2016
DOI: 10.7884/teke.627
|View full text |Cite
|
Sign up to set email alerts
|

Di̇asporada Karaçay Türkçesi̇ni̇n Kullanimi Eski̇şehi̇r Örneği̇

Abstract: Bu yazıda bir diaspora lehçesi olan Karaçay Türkçesinin Eskişehir ilindeki kullanımı üzerinde durulacaktır. Rus zulmü nedeniyle Kafkaslardaki ata yurtlarından çıkartılan Karaçaylar, Anadolu topraklarına üç büyük dalga hâlinde göç etmişlerdir. Bu göçlerle gelen Karaçaylar; Ankara, Eskişehir, Afyon ve Tokat illerindeki köylere yerleştirilmiştir. Kültürlerine son derece bağlı olan Karaçaylar, yerleştikleri yerlerde uzun süre dillerini ve kültürlerini koruyarak millî benliklerinden kopmamışlardır. Ancak zamanla di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Karachay-Balkar dialect spoken in Russia has been cited as a vulnerable language by UNESCO, namely the language is acquired by children but its usage is restricted to certain domains. A recent study on the Karachay-Balkar dialect spoken in Eskişehir (Boz and Günay Aktaş 2016) has revealed that the dialect is hardly ever spoken by 1-20 year-old generation and it is restricted to home with 30 year-old and above generation. Our recording sessions with speakers from Konya have also shown that only the oldest generation is fluent in the language.…”
Section: Introductionmentioning
confidence: 99%
“…Karachay-Balkar dialect spoken in Russia has been cited as a vulnerable language by UNESCO, namely the language is acquired by children but its usage is restricted to certain domains. A recent study on the Karachay-Balkar dialect spoken in Eskişehir (Boz and Günay Aktaş 2016) has revealed that the dialect is hardly ever spoken by 1-20 year-old generation and it is restricted to home with 30 year-old and above generation. Our recording sessions with speakers from Konya have also shown that only the oldest generation is fluent in the language.…”
Section: Introductionmentioning
confidence: 99%